2022
DOI: 10.3819/ccbr.2022.170004
|View full text |Cite
|
Sign up to set email alerts
|

Elephants and Sirenians: A Comparative Review across Related Taxa in Regard to Learned Vocal Behavior

Abstract: Vocal production learning is the ability to modify a vocal output in response to auditory experience. It is essential for human speech production and language acquisition. Vocal learning evolved independently several times in vertebrates, indicating evolutionary pressure in favor of this trait. This enables cross-species comparative analysis to be used to test evolutionary hypotheses. Humans share this ability with a versatile but limited group of species: songbirds, parrots and hummingbirds, bats, cetaceans, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Many studies have established sound navigation and ranging (SONAR) scans as a valuable method of underwater detection of Antillean manatees (T. m. manatus) in their turbid waters of Mexico and Central America, with manatee detection frequencies of up to 93% (Gonzalez-Socoloske et al, 2009;Gonzalez-Socoloske and Olivera-Gomez, 2012;Guzman and Condit, 2017;Puc-Carrasco et al, 2017;Castelblanco-Martıńez et al, 2018). In addition, manatees produce a variety of vocalizations including squeaks, screeches, whines, and trills (Umeed et al, 2018;Brady et al, 2020;Baotic et al, 2022) shown to be important for their underwater communication and emitted across various behavioral states (Bengtson and Fitzgerald, 1985;O'Shea and Poche, 2006;Brady et al, 2021). Passive acoustics have been used in many studies to monitor manatees and have yielded up to 100% detection frequencies (LaCommare et al, 2008;Kikuchi et al, 2013;Rivera Chavarria et al, 2015;Rycyk et al, 2021;Rycyk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have established sound navigation and ranging (SONAR) scans as a valuable method of underwater detection of Antillean manatees (T. m. manatus) in their turbid waters of Mexico and Central America, with manatee detection frequencies of up to 93% (Gonzalez-Socoloske et al, 2009;Gonzalez-Socoloske and Olivera-Gomez, 2012;Guzman and Condit, 2017;Puc-Carrasco et al, 2017;Castelblanco-Martıńez et al, 2018). In addition, manatees produce a variety of vocalizations including squeaks, screeches, whines, and trills (Umeed et al, 2018;Brady et al, 2020;Baotic et al, 2022) shown to be important for their underwater communication and emitted across various behavioral states (Bengtson and Fitzgerald, 1985;O'Shea and Poche, 2006;Brady et al, 2021). Passive acoustics have been used in many studies to monitor manatees and have yielded up to 100% detection frequencies (LaCommare et al, 2008;Kikuchi et al, 2013;Rivera Chavarria et al, 2015;Rycyk et al, 2021;Rycyk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%